Research on the Innovative Inheritance Application of Artificial Intelligence Technology in Traditional Music Education and Strategies to Enhance the Aesthetic Experience - Ning Li (International Journal of Computer Information Systems and Industrial Management Applications, 2025)
With the deep integration of digital technology and traditional art, artificial intelligence (AI) provides new momentum for the innovative development of traditional music education. This paper focuses on the cultural inheritance and aesthetic nurturing demands of traditional music education, systematically analyzes the inheritance and innovation application strategies of AI technology in traditional music education, constructs a music automatic generation model based on Leak-GAN, and conducts experimental investigations on students' aesthetic sports in music education. The results of the study show that the music melodies generated by the Leak-GAN model in this paper have obtained general listeners' ratings of 4.1, 4.1, and 3.9 in the aspects of coherence, pleasantness, and innovativeness, respectively, and professionals' ratings of 3.9, 4.1, and 3.5, which are better than those of other comparative models. The expert group students scored significantly higher than the novice group in music aesthetics, emotional experience, and music-induced arousal, indicating that music training can regulate the aesthetic judgment of music, enhance the pleasurable experience, and is an important part of enhancing the effect of music aesthetics. This paper is of great practical significance for the inheritance and innovation of AI technology in music education and the development of strategies to enhance students' aesthetic experience.